How does 2-(1+lnx) equal 1-lnx? More questions about Science & Mathematics, how. Ask Monti Moreno. ... ^2 and dv/dx 1 So u=(ln x)^2 and v=x Integrate by ...
Read more

Positive: 53 %

Is the integral of $\frac{1}{x}$ equal to $\ln(x) ... \ln x + c_1 & \text{if } x > 0, \\ \ln (-x) + c_2 ... answer doesn't make so much sense. There's no ...
Read more

Positive: 50 %

More resources

... y = x/lnx is deﬁned on 0 < x < ∞, except for x = 1. y′ = lnx −1 (lnx)2 Thus, y ... x3 +2 diverges, by comp.test, and so does Z ...
Read more

Positive: 53 %

How does e^x equal a natural logarithm? ... Plot the functions e^x & ln(x) ... Algebra 1/2 Math Word Problem Solution Method Factoring Flow Chart Log Rules ...
Read more

Positive: 48 %

... (x+1)^2 =2. We know that ln x^y = y ln x ==> ln (x+1)^2 = 2*ln (x+1) = 2. Now divide by 2: ==> ln (x+1) = 2/2=1 ==> x+1 = e^1 = e ... How long does ...
Read more

Positive: 34 %

ln(x)=ln(2x-1)-ln(x-2) ln(x)=ln[(2x-1)/(x-2)] x=(2x-1)/(x-2) x(x-2)=2x-1 x^2-2x=2x-1 x^2-2x-2x+1=0 x^2-4x+1=0 Answer: x = 2+sqrt(3) or x = 2-sqrt(3)
Read more

Positive: 11 %

Show more results

If it doesn't, what does it equal? Help; Save? ... Does (ln x)^2 = ln x^2? ... 1. Originally Posted by DivideBy0.
Read more

Positive: 53 %

I figured it would just be $0$ since $\frac{1}{\ln(\infty)}$ should equal $0$. ... Why does $x^{(1/\ln(x))} ... 4,678 2 8 25. asked Sep 11 '14 at ...
Read more

Positive: 52 %

Natural Logarithm - ln(x) ... when x approaches infinity is equal to infinity: lim ln(x) = ∞, ... -2,-1,0,1,2,...): Log z = ln(r) ...
Read more

Positive: 47 %

... (lnx)=1/(lnx)*1/x=1/(xlnx) ... What is the derivative of #5+2lnx#? How do you find the second derivative of # ln(x^2+9)# ? ...
Read more

Math2.org Math Tables: Integral ln(x) Discussion of ln(x) dx = x ln(x) - x + C. 1. Proof. ... = ln(x) x - x (1/x) dx = ln(x) x - dx = ln(x) x - x + C
Read more

Positive: 17 %

Get an answer for 'Find the derivative of the function y = lnx/1+lnx?' and find homework help for other Math questions at eNotes
Read more

Positive: 10 %

... x+4)/(x+1)])=exp(Lnx) (x+4)/(x+1)=x x+4=x(x+1) x+4=x^2+x 4=x^2 x=+-2 x ... How do you solve #ln(x+4)-ln(x+1) = lnx#? ... does the phosphorus ...
Read more

Read more

53 %